Pengaruh Pengungkapan CSR terhadap Nilai Perusahaan dengan Usia dan Ukuran Perusahaan Sebagai Variabel Moderasi - Kesumastuti, Made Ayu Riski Meinanda; Dewi, Ayu Aryista (E-Jurnal Akuntansi, 2021)
The purpose of this study is to determine the influence of Corporate Social Responsibility Disclosure on Corporate Values, then to find out the influence of company age and company size in strengthening the influence of Corporate Social Responsibility disclosure on corporate values.  The population used in this study is Manufacturing companies listed on the Indonesia Stock Exchange.  The company in this study was selected using purposive sampling techniques in accordance with the criteria that have been set, and obtained as many as 30 samples of companies. The analysis technique used is moderation regression analysis. The results of the analysis showed that CSR disclosure positively affects the value of the company, then the age of the company and the size of the company can moderate the influence of Corporate Social Responsibility on the value of the company. Keywords: CSR Disclosure; Firm Value; Firm Age; Firm Size.